Effects of reverse seasonal submersion on the germination and persistence of soil seed banks in hydro‐fluctuation belts. Issue 7 (20th July 2018) - Ma, Yanran; Chen, Fangqing; Chen, Shaohua; Guan, Shoupeng; Chen, Chen
Abstract: The construction of the Three Gorges Dam has resulted in the occurrence of reverse seasonal water‐level fluctuations. The species composition and quantity of riparian soil seed banks collected from four hydro‐fluctuation belts were assessed by simulating different submersion cycles to determine the effects of reverse seasonal water‐level fluctuations on the germination and persistence of soil seed banks in the Three Gorges Reservoir Region. Results showed the number of species that germinated from the soil seed bank decreased with submersion. The number of germinated seeds in soil seed banks after submersion for 7 months in Xingshan, Zigui, Wanzhou, and Zhongxian decreased by 60%, 53%, 57%, and 57%, respectively, relative to the control. The species diversity index and seed density of germinated seeds in soil seed banks also significantly decreased with prolongation of submersion time. Seed density decreased by 93%, 83%, 76%, and 72%, respectively, after 7 months of submersion. Species composition and dominance within the soil seed bank changed over time due to submersion. In general, reverse seasonal submersion negatively impacts the germination and persistence of soil seed banks. The response of soil seed bank germination and persistence to reverse seasonal submersion became the key factor determining the heterogeneity in the spatial distribution of the soil seed bank in hydro‐fluctuation belts due to the large differences in submersion time between areas at various elevations.